Self-consciousness: an I-World patterned process model - Díaz, José-Luis (Adaptive behavior, 2018)
The self is herein recognized as self-consciousness, a broad dynamic system of self-recognition and self-reference. Eight psychosomatic and extended cognitive functions working as an interactive whole are proposed to constitute self-consciousness: (1) somatic domain and body image; (2) situation and domestic range; (3) agency and power to act; (4) introspection, mindfulness, and metacognition; (5) first person discourse and appropriation; (6) episodic memory, autobiography, and role; (7) attribution and alterity; (8) conscience, moral consciousness, and ethical stance. These functions, complemented with considerations about depersonalization and selflessness, are briefly defined and described. These subsystems may work independently but they may interact and variably coalesce according to the demands of the task. Since self-awareness would require a dynamic swarm-like activation pattern of the cluster, the self does not reside in particular brain sites or networks but depends on top-down and bottom-up mechanisms coupled with incoming and outgoing sensory-motor data loops. This psychophysical theory avoids the swing between internal and external elements in favor of an embracing I-World patterned process that comprises neural, bodily, behavioral, environmental, and social dimensions converging in the construction and expression of self-conscious and personal identity experiences integrated by a participant brain.